Analysis of case splitting in a arithmetical system - Tigran M. Galoyan (Изд-во НАН РА)
Investigations in this paper concern the analysis of case splitting [(: A ! B) ! (A ! B) ! B] in an arithmetical system. It is shown that the case splitting can be done according to a thicker class of formulas (quantifer-free formulas) instead of decidable formulas. The latter includes the class of quantifer-free formulas. Some approaches to the case splitting, promoted by other authors, have been investigated, and some corrections concerning the selection of quantifer-free formulas instead of decidable formulas have been done. According to these corrections, a new derivation of case splitting is suggested.
Keywords: Mathematics